Penampilan Bawang Merah Pada Kawasan Rumah Pangan Lestari (KRPL) Di Pulau Punjung Kabupaten Dharmasraya - Misran, Misran (Jurnal Penelitian Pertanian Terapan, 2015)
To support the growth of onion plants are optimal, the price factor is one of the easiest growth factors and factors of the environment that can be modified through fertilization.The used of fertilizers with the right amount could be increased plant growth. This research aims to get the best fertilizers on the growth and yield of onion. The experiment was conducted at farmers yard members of KRPL Ranah Lintas, Pulau Punjung District, Dharmasraya Regency, from June to October 2012. The experiment was arranged in a Randomized Block Design (RBD), with involving five farmers as replication, where the sub-sample of each farmer 2 times so that the experimental units totaling 50 units. Seeds of onion used are varieties of Bima (derived from Balitsa Lembang), planted in polybags size 30 x 35 cm, before cutting the seedlings planted in the upper third. The treatments tasted were; (A) 0.0 g / pot equivalent to 0 kg/ha, (B) 0.375 g/pot equivalent to 125 kg/ha, (C) 0.75 g / pot equivalent to 250 kg/ha, (D) 1,125 g/pot equivalent to 375 kg/ha, and (E) of 500 kg / ha or 1.5 g/pot equivalent to 500 kg/ha. As a basic fertilizer used cow manure 20 t, Urea 150 kg, and SP36 200 kg / ha. The results showed that no significant effect on plant height and weight of a small bulb. The highest weight bulb/pot obtained of KCl giving 0.375 g/pot with the average weight of bulb/pot 50.65 g. The results suggested that to obtain optimal growth and yield of onion in this location (KRPL) of KCl should be given at a dose of 0.375 g/pot equivalent to 125 kg / ha. Keywords: Onion, KRPL, KCl